Any other name [large type] : a Longmire mystery - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2014)
"A sheriff's mysterious death spurs the new novel in the New York Times bestselling Walt Longmire series Sheriff Walt Longmire had already rounded up a sizable posse of devoted readers when the A&E television series Longmire sent the Wyoming lawman's popularity skyrocketing. Now, with three consecutive New York Times bestsellers to his name and the second season of Longmire reaching an average of 5.4 million viewers per episode, Craig Johnson is reaching a fan base that is both fiercely loyal and ever growing. In Any Other Name, Walt is sinking into high-plains winter discontent when his former boss, Lucian Conally, asks him to take on a mercy case in an adjacent county. Detective Gerald Holman is dead and Lucian wants to know what drove his old friend to take his own life. With the clock ticking on the birth of his first grandchild, Walt learns that the by-the-book detective might have suppressed evidence concerning three missing women. Digging deeper, Walt uncovers an incriminating secret so dark that it threatens to claim other lives even before the sheriff can serve justice--Wyoming style"--